Investigations of the historic textiles excavated from Ancient Ainos (Enez - Turkey) by multiple analytical techniques - Çakan, Banu; Başaran, Sait; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2014)
Some metal ornamented textile specimens and a textile button, excavated from Ancient Ainos (Enez Turkey), have been investigated using FTIR and EDXRF spectrometry, for the purpose of material identification. FTIR spectral results indicated that textiles were made from partially degummed Bombyx mod silk. The IR spectral investigation of the textile button revealed that some cellulose fillings were used inside the button. The EDXRF analysis of the metal ornaments showed that they were silver plated copper. Surface morphology of the textiles and the metal ornaments were investigated by SEM images. It was shown that textile fibers were highly degraded. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bombyx mori silk; EDXRF; FTIR spectroscopy; Historic textiles; Ft-Ir Spectroscopy; Mori Silk Fibroin; Bombyx-Mori; Secondary Structure; Infrared-Spectroscopy; Fibers; Proteins; Sericin; Films; Spectra